2000
DOI: 10.1002/1522-2683(20000601)21:11<2170::aid-elps2170>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of rat serum V: Adjuvant arthritis and its modulation by nonsteroidal anti-inflammatory drugs

Abstract: The effect of adjuvant arthritis (AA) on the pattern of rat serum proteins includes the upregulation of haptoglobin, orosomucoid, alpha2-macroglobulin, serine protease inhibitor-3, thiostatin, alpha1-antitrypsin, C-reactive protein, and the downregulation of kallikrein-binding protein, alpha1-inhibitor III, apolipoprotein A-I, alpha2-HS-glycoprotein, albumin, apolipoprotein A-IV, transthyretin and transferrin. Minor changes (+/- 20%) are observed for Gc-globulin, ceruloplasmin, and alpha1-macroglobulin. AA thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 89 publications
2
18
0
Order By: Relevance
“…Studies by Gianazza et al on rat serum identified 34 proteins with human homologues and concluded that even abundant proteins could be markers for disease states [30][31][32]. Traditionally, it was believed that the only source of Immunoglobulins (IgGs) was mature B lymphocytes, but recently, some researchers have reported that IgG could also be detected in carcinoma cells derived from epithelium [33].…”
Section: Discussionsupporting
confidence: 83%
“…Studies by Gianazza et al on rat serum identified 34 proteins with human homologues and concluded that even abundant proteins could be markers for disease states [30][31][32]. Traditionally, it was believed that the only source of Immunoglobulins (IgGs) was mature B lymphocytes, but recently, some researchers have reported that IgG could also be detected in carcinoma cells derived from epithelium [33].…”
Section: Discussionsupporting
confidence: 83%
“…Most analytical procedures were as previously described [1,2,4,5,8]. 2-DE maps were obtained by IPG-DALT [9].…”
Section: Electrophoretic Techniquesmentioning
confidence: 99%
“…[26], provides no information of the possible influence of ethnic origin, although data are subdivided by gender and age. An extensive survey on minor protein components in human serum has been undertaken by Leigh Anderson et al (oral communication at 4th Siena Meeting "From Genome to Proteome: Knowledge Acquisition and Representation", Sept. [4][5][6][7]2000). When testing over a larger genetic distance (Mus musculus and Mus spretus vs. two strains), Klose and co-workers detected more than 1000 variant protein spots (in brain, heart, and skeletal muscle) between the two subspecies [27,28].…”
Section: Interstrain Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of rat serum by 2-DE thus provides a very sensitive way to monitor onset and progression of any pathological state involving an inflammatory component as well as to assess the outcome of any therapeutic intervention. We could validate such principles in a few model systems (various types of experimentallyinduced inflammation [5][6][7], a genetically-determined susceptibility to cerebro-vascular disease [8][9][10][11]). We could then apply similar concepts to the analysis of cerebrospinal fluid (CSF) proteome [12].…”
Section: Anniversariesmentioning
confidence: 99%